Prolonged Soil Frost Affects Hydraulics and Phenology of Apple Trees - Beikircher, Barbara; Mittmann, Claudia; Mayr, Stefan (Frontiers in Plant Science, 2016)
Restoration of an adequate water supply in spring is a prerequisite for survival of angiosperm trees in temperate regions. Trees must re-establish access to soil water and recover xylem functionality. We thus hypothesised that prolonged soil frost impairs recovery and affects hydraulics and phenology of Malus domestica var. ‘Golden Delicious’. To test this hypothesis, over two consecutive winters the soil around some trees was insulated to prolong soil frosting, From mid-winter to early summer, the level of native embolism, the water and starch contents of wood, bark and buds were quantified at regular intervals and findings correlated with various phenological parameters, xylogenesis and fine root growth. The findings confirm that prolonged soil frost affects tree hydraulics and phenology but the severity of the effect depends on the climatic conditions. In both study years, percentage loss of hydraulic conductivity (PLC) decreased from about 70% at the end of winter to about 10% in May. Thereby, xylem refilling strongly coincided with a decrease of starch in wood and bark. Also treated trees were able to restore their hydraulic system by May but, in the warm spring of 2012, xylem refilling, the increases in water content and starch depolymerisation were delayed. In contrast, in the cold spring of 2013 only small differences between control and treated trees were observed. Prolongation of soil frost also led to a delay in phenology, xylogenesis and fine root growth. We conclude that reduced water uptake from frozen or cold soils impairs refilling and thus negatively impacts tree hydraulics and growth of apple trees in spring. Under unfavourable circumstances, this may cause severe winter damage or even dieback.